Kinerja Sistem Informasi Manajemen Pelayanan Publik Pemerintah Kota Pekalongan - Mohamad Ichsana Nur; Peny Novarina (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
The City of Pekalongan is one of economic growth hubs in Central Java. Pekalongan possesses a classic issue like an overweight and inefficient bureaucracy, lack of innovation, dissatisfaction of public service, and so on. The government then proceeds digital-based budget so that it succeeds to push public spending. This paper aims to provide an overview of Pekalongan City Government Performance Management in implementing Management Information Systems (MIS) for Public Services. The analysis uses various theoretical perspectives on public sector performance management, public services and public service performance innovation. This research is a descriptive study with data collection techniques using non-reactive content analysis through secondary data and documents that already exist. The analysis shows that the application of technology to the Pekalongan City government innovation performance can save energy, time and budget. Performance monitored through the system from planning to implementation can be monitored through information technology innovation. Thus, an efficient, fair, responsive, accountable public service system can be more easily achieved.